The economy of renaissance Italy - Malanima, Paolo (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Drawing on a wide range of literature and adopting a macroeconomic approach, this book provides a comprehensive overview of the Italian economy during the Renaissance, focusing on the period between 1348, the year of the Black Death, and 1630. The Italian Renaissance played a crucial role in the formation of modern world, with developments in culture, art, politics, philosophy and science sitting alongside, and overlapping with, significant changes in production, forms of organisation, trades, finance, agriculture and population. Yet it is usually argued that splendour in culture coexisted with economic depression: that the modernity of Renaissance culture coincided with an epoch of epidemics, famines, economic crisis, poverty and destitution. This book examines both faces of the Italian economy during the Renaissance showing that capital per worker was plentiful and productive capacity and incomes were relatively high. The endemic presence of the plague, curbing population growth, played an important role in this. It is also shown that the organisation of production in industry and finance, consumerism, human capital and mercantile rationality were forerunners of modern-day capitalism. This book is an invaluable resource for scholars and students of the Renaissance and Italian economic history. Paolo Malanima is an economic historian. He has been Director of the Institute of Studies on Mediterranean Societies (ISSM-CNR) in Naples, Italy, and Professor of Compared Economies and Growth Economics in Magna Graecia University in Catanzaro. His main research interests span the long-term Italian economy and past and present energy consumption"--
Keywords: Italy -- Economic conditions -- 14th century; Italy -- Economic conditions -- 15th century; Italy -- Economic conditions -- 16th century; BUSINESS & ECONOMICS / Economic History; BUSINESS & ECONOMICS / Economics / General; HISTORY / Europe / Italy